The Effect of Drying Treatment on Pytochemical Content and Antioxidant Capacity of Broccoli (Brassica oleacea L.) By Using a Cabinet Dryer - Mazarina Devi; Soenar Soekopitojo; Heri Pratikto; Aji Prasetya Wibawa; Mansoor Abdul Hamid (2022)
Broccoli (Brassica oleacea L.) can be classified as a good value of agriculture product that contains high amount of active compounds but it is easily damaged due to improper handling and processing practices. A part of the flowers, its leaves and stems are also valuable parts but it's always through away during harvesting. The purpose of this study is to determine the quality of broccoli flower and its by-product after undergo drying treatment in cabinet dryer. The treated samples were then measured their phytochemical content and antioxidant capacity and all data obtained were analyzed by using ANOVA. The results showed that the dried broccoli leaf content the highest amount of vitamin C (8.11mg/100g), chlorophyll (1816.03mg/kg), phenolic (2.37%), flavonoid (1,40550%), and antioxidant capacity (25.92ppm) compared to its flower and stem. This finding indicated that drying process can retained the good quality of broccoli with minimum deterioration of active compounds and broccoli leaves shows high active compounds and can be utilize as food or food ingredient that are beneficial to our health.